The role of financial analysis using financial models to predict the financial stumble on the Saudi public utilities sector: An applied study - Abdulrahman, Najla Ibrahim; Alkhamis, Fatimah Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aimed to find out the role of financial analysis using financial models to predict the financial stumble on the Saudi public utilities sector. The study was based on the financial analysis of the financial lists published by the sample of the study of the Gas and Manufacturing Company (Gasco) and the Saudi Electricity Company listed in the Saudi Capital Market Authority. During the period (2009-2018) I followed the descriptive analytical approach. The study found the effectiveness of the Abdul Rahman model to predict the financial stumble on the public utilities sector, and the low effectiveness of the Altman model and the Kida model to predict financial stumbles on the utility sector. The study also recommended encouraging audit offices to add financial analysis services to the possibility of predicting and addressing financial stumbles, directing companies using financial models that help predict financial stumbles, encouraging investors to use financial models that help predict financial stumbles to make the right decision, and directing researchers in the study of financial default forecasting on the insurance sector using the Abdul Rahman model.
Keywords: prediction of financial failure; financial analysis; financial ratios